EFISIENSI ANGGARAN BIAYA PRODUKSI TERHADAP PENGENDALIAN BIAYA PRODUKSI PADA CAHAYA FURNITURE JATI - Maya Novianti (Politeknik Raflesia Press, 2020)
The budget becomes very important as a center of accountability that is used to control activities, namely comparing the predetermined budget with its implementation. Then if there are deviations, the deviation is analyzed so that the causes are known and improvements can be made in the future. This is done so that the company can carry out efficiency in production costs so that there is no waste which will result in the selling price and profits that the company gets. The difference in production costs for a set of 2111 brick pyramid minimalist guest chairs is 2% of the standard cost of IDR 3,783,000 while the actual production cost for a set of 2111 brick pyramid minimalist guest chairs is IDR 3,699,343. Standard production costs at the dining table minimalist seat 6 is IDR 5,521,500 while the actual cost is IDR 5,339,543 so that the variance or the difference is 3%. For the difference in production costs on a minimalist box bed set is 7% of the standard production cost of IDR 3,894,000 while actualization The production cost for producing a set of minimalist box bed is Rp. 3,607,551. The standard production cost for producing a set of 3 door wardrobes is Rp. 4,790,000 while the actual production cost is Rp. 4,373,891 with a variance or difference of 9%. The variance or the difference in the production cost of a half-circular set of minimalist toalets is 9% where the standard production costs are equal r IDR 3,584,417 and the actual production cost is IDR 3,268,081.